Cultural, Class, or Scientific Aspirations? Polish Jews at the University of Padua - Marchel, Sławomir (Perspektywy Kultury, 2023)
Among the students of medicine in Padua from the Polish-Lithuanian Commonwealth, in XVII and XVIII centuries, we can note a certain number of Jews. This article contains a short analysis of so far findings in the area of research on this aspect of Jewish history in the First Republic of Poland. Referring to more and less known facts, the Author paid particular attention to the motivations and aspirations of Jewish scholars who had come to City of Antenor from Polish-Lithuanian land. Following the careers of Jewish medical graduates, we can see, that for most of them having a Padua diploma was not only the way to gain a better status in the Jewish community but also a gateway to overcoming cultural barriers. According to the Author, this was possible due to the fact, that many of the representatives of polish nobility, who were called “Paduans,” had similar experiences of contact with the university environment and the culture of the Venetian Republic.